Advances in Poultry Nutrition Research - Kumar Patra, Amlan (IntechOpen, 2021)
Due to the wide acceptance of poultry meat and eggs, poultry farming is the fastest growing global livestock industry. Nutrition plays a vital role in economic production and the maintenance of proper poultry health. Therefore, there is a great need to update balanced nutrient requirements for new breeds, utilize alternative feed resources, evaluate newer feed additives to optimize production while excluding antimicrobial feed additives and maintain overall health. The first section of this book contains six chapters that discuss the utilization of unconventional feeds, nanominerals to reduce mineral proportions in diets, and water intake affected by environmental temperature. The second section contains six chapters that describe proper nutritional management to improve gut health and immunity, the prevention of common diseases, and the amelioration of heat stress in poultry.